2020
DOI: 10.1088/1755-1315/433/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of plant nutrition using non-traditional organic fertilizers and zeolite-containing tripoli

Abstract: The problem of conservation and reproduction of soil fertility by using unconventional organic fertilizers, particularly the replacement of the mineral nitrogen fertilizer to its organic form is discussed. The growth of the livestock industry lays the groundwork for the recovery of meat processing industry waste of horned ungulate crumbs (HAC) as fertilizer for inter-tilled crops. HAC contains about 14% nitrogen. Experiments on the application of HAC as a nitrogen fertilizer and sorption-type ameliorant – zeol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Among agricultural wastes, meat and bone meal, a byproduct of the animal rendering industry, contains significant amounts of essential nutrients for plants, especially N, P, and Ca [28,29]. Several publications have presented the use of waste from the meat industry as a source of nutrients in crop fertilisation [30][31][32][33]. Our research evaluates the potential use of MBM in crop production, not only as a source of nutrients to improve soil nutrient abundance [34] but also to improve grain quality, elements often overlooked when evaluating applied organic fertilisers.…”
Section: Introductionmentioning
confidence: 99%
“…Among agricultural wastes, meat and bone meal, a byproduct of the animal rendering industry, contains significant amounts of essential nutrients for plants, especially N, P, and Ca [28,29]. Several publications have presented the use of waste from the meat industry as a source of nutrients in crop fertilisation [30][31][32][33]. Our research evaluates the potential use of MBM in crop production, not only as a source of nutrients to improve soil nutrient abundance [34] but also to improve grain quality, elements often overlooked when evaluating applied organic fertilisers.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous results of scientific research on the cultivation of agricultural crops using only organic fertilizers (semi-rotted manure, compost, peat), urban wastewater sludge, as well as by-products of the food industry and waste processing (liquid and solid products of a biogas plant, horn-hoofed shavings, bone meal, cake, etc.) showed their high economic efficiency [1], [2], [3], [4], [5], [6], [8], [9], [12], [ 19], [20], [21]. The research carried out in greenhouses showed that by-products of industrial production, i.e., products of a biogas plant, municipal wastewater sludge, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Disposal of waste from light industry around the world causes not only a burden on the environment, but also additional production costs. Wastes such as municipal sewage sludge, hoof shavings, biogas plant waste can be effectively used as organic fertilizers [1,6,7,8,12]. One of these wastes, or residues, of dairy production is cake -a hydrophobic viscous substance of light gray color with a sharp and unpleasant smell of spoiled cottage cheese.…”
Section: Introductionmentioning
confidence: 99%